Bromatological chemical study and phytochemical screening of fruit from Pourouma cecropiifolia c. Martius “uvilla” - Arias Arroyo, Gladys C. (2011)
The specie Pourouma cecropiifolia C.martius (Uvilla), whose habitat is the tropic, it is also known as “uvilla”, “uva caimanera”, “ caimaron”, “caima” y “puruma “. It presents content of water 84,50 grams percent. In dry sample: ethereal extract 0,91; total protein 2,06; ash 1,81; crude fiber 5,42; carbohydrates 88,84 grams percent. Vitamin B1 0,58; vitamin B2 1,42; vitamin C 3,10 milligrams percent. Also are present in dry sample: calcium 154,84; hierro 3,87; phosphorus 64,52 milligrams percents. It is a fruit which can be used as important source of nutrients, mainly vitamins C, B1, B2 and the minerals such as calcium, phosphorus and iron. The phytochemical screening have detected the presence of phenolic compounds, flavonoids, tannins, alkaloids y steroids.